2019
DOI: 10.1111/scd.12370
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of saliva substitutes and stimulants in the treatment of dry mouth

Abstract: Aims To evaluate the efficacy of saliva substitutes and stimulants compared to placebo in improving findings of dry mouth not caused by Sjӧgren's. Methods and Results Four databases were searched (PubMed, Web of Science, Cochrane Library, and EMBASE) through March 2018. Only randomized controlled trials (RCT) using placebo interventions with dry mouth patients were included. Outcomes included salivary flow and self‐reported patient improvement. The Cochrane Collaboration's tool for assessing risk of bias was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Formulations with active stimulants or medicines are beyond the scope of this review. Complementary reviews that focus on therapeutic trials of salivary substitutes are available (Assery, 2019; Brennan, Shariff, Lockhart, & Fox, 2002; Furness, Worthington, Bryan, Birchenough, & Mcmillan, 2011; Salum et al, 2018; See, Mohammadi, Han, Mulligan, & Enciso, 2019). Abbreviations used throughout this review article are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Formulations with active stimulants or medicines are beyond the scope of this review. Complementary reviews that focus on therapeutic trials of salivary substitutes are available (Assery, 2019; Brennan, Shariff, Lockhart, & Fox, 2002; Furness, Worthington, Bryan, Birchenough, & Mcmillan, 2011; Salum et al, 2018; See, Mohammadi, Han, Mulligan, & Enciso, 2019). Abbreviations used throughout this review article are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of radiation to treat malignant pathologies of the upper aerodigestive tract, the patient will suffer loss of 50-70% of saliva function if 10-15 Gy of radiation is applied or even worse it is undetectable when higher doses of radiation (40-42 Gy) is given to the patient [37]. There have been numerous published studies on the efficacy of saliva substitute in treating xerostomia [14,[38][39][40][41][42][43][44]. Studies that looked into the efficacy of Oral7® mouthwash in treating xerostomia in post radiotherapy patients is, however scarce [21].…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia greatly impact the patient's quality of life ( Porcheri and Mitsiadis, 2019 ). The available treatments for SG atrophy are temporary and limited to systemic parasympathomimetic drugs such as pilocarpine, sialogogues, and artificial saliva substitutes and SG is not regenerate functionally ( See et al., 2019 ). New therapeutic options have shifted to regenerating SG cells by stem cell transplantation ( Lombaert et al., 2017 ; Kim et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple treatment options for SG hypofunction such as systemic parasympathomimetic, sialogogues, and artificial saliva substitutes their effect are challenging. Common treatment strategies for SG hypofunction are temporary and the SGs are not restored functionally ( See et al., 2019 ). Stem cell-based therapy has been recently introduced for treatment of SGs hypofunction ( Sui et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%